Interstitial Nephritis in a Patient with Inflammatory Bowel Disease - Payaswini Vasanth; Michelle Parmley; Jose Torrealba; Tamim Hamdi (Case Reports in Nephrology)
Tubulointerstitial nephritis in patients with inflammatory bowel disease has been linked to the use of 5-ASA derivatives. Various aspects of this theory have been challenged with a potential role for the underlying autoimmune disorder. Steroids are the mainstay of treatment and mycophenolate mofetil might be an effective alternative. We report a patient who responded well to mycophenolate despite continuing mesalamine, the suspected offending agent.